Pengaruh Kecepatan Pengadukan Terhadap Sintesis Biodiesel Dari Minyak Jarak Menggunakan Katalis La/NZA - Putri Azizah; Syaiful Bahri; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Biodiesel is one of alternative energy to replace fossil fuels from vegetable oil. The aims of this research were to produce biodiesel from castrol oil using heterogen catalyst La/NZA, to studythe effect of agitation speed and the ratio of impregnation La on NZA to the yield of biodiesel and to determine the characteristics of catalyst and biodiesel. The La/NZA catalyst is made bygrinding the natural zeolite to a size of -100 + 200 mesh, then the zeolite is activated using solution of HCL and NH4Cl, then it was dried. La is impregnated into NZA then dried using ovenand calcination. Production of biodiesel is carried out through two stages: esterification and trans-esterification. Before esterification, degumming process was done to remove impuritiesand gum contained in the oil. While in the trans-esterification process, variation of impregnation La on NZA are 0% La, 1% La and 3% La and variation of agitation speed are 300 rpm, 400 rpmand 500 rpm for 80 grams of castrol oil and methanol with the ratio of oil : methanol 1 : 9 was inserted to trans-esterification reactor, reaction lasted for 120 minutes at 60ºC. The highest yieldresulted on using 3%La/NZA catalyst with agitation speed 400 rpm which is 88.15%. Characteristics of the catalyst that has a surface area and ratio of Si/Al are large enough withbiodiesel produced in accordance with predefined standards (SNI 04-1782-2015).Keywords: biodiesel, La/NZA, castrol oil, transesterification.